Pengaruh Kontribusi Pajak Restoran Terhadap Pendapatan Asli Daerah Di Kota Bandung - Ayudya Renindita; Ira Novianty (Indonesian Accounting Research Journal, 2020)
Based on law number 12 of 2008 concerning Regional Government, it provides opportunities and flexibility for regional governments to be able to develop their regions to the maximum, or commonly known as regional autonomy. The purpose of this study is to determine the effect of restaurant tax contributions on local revenue in the city of Bandung. This study used a quantitative descriptive method with a sample size of 96 months. The type of data used is quantitative data with secondary data from the Regional Revenue Management Agency and the Bandung City Financial and Asset Management Agency. The results of this study indicate that restaurant tax has a partially significant effect on local revenue in the city of Bandung. The Adjusted R Square value of 0.595 means that local revenue is affected by 59.5% by restaurant tax and the remaining 40.5% is influenced by other variables not examined in this study.